MENA confers resistance to paclitaxel in triple-negative breast cancer - Oudin, Madeleine J. (Mol Cancer Ther, 2016)
Taxane therapy remains the standard of care for triple-negative breast cancer. However, high frequencies of recurrence and progression in treated patients indicate that metastatic breast cancer cells can acquire resistance to this drug. The actin regulatory protein MENA, particularly its invasive isoform, MENA(INV), are established drivers of metastasis. MENA(INV) expression is significantly correlated with metastasis and poor outcome in human breast cancer patients. We investigated whether MENA isoforms might play a role in driving resistance to chemotherapeutics. We find that both MENA and MENA(INV) confer resistance to the taxane paclitaxel, but not to the widely used DNA damaging agents doxorubicin or cisplatin. Furthermore, paclitaxel treatment does not attenuate growth of MENA(INV)-driven metastatic lesions. Mechanistically, MENA isoform expression alters the ratio of dynamic and stable microtubule populations in paclitaxel-treated cells. MENA expression also increases MAPK signaling in response to paclitaxel treatment. Decreasing ERK phosphorylation by co-treatment with MEK inhibitor restored paclitaxel sensitivity by driving microtubule stabilization in MENA isoform-expressing cells. Our results reveal a novel mechanism of taxane resistance in highly metastatic breast cancer cells and identify a combination therapy to overcome such resistance.